Pengaruh Diameter Belitan Ground Strap Terhadap Perbandingan Udara-Bahan Bakar (AFR) dan Konsumsi Bahan Bakar Spesifik (SFC) Pada Mesin Spark Ignition 150cc - Paloboran, Marthen; Pangruruk, Thesya Atarezcha (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2025)
The primary objective of this study is to evaluate the impact of providing a ground strap on the spark plug cable with varying diameters of the ground strap winding at 0.3, 0.6, and 0.9 mm. The evaluation was conducted on a 150 cc single-cylinder spark ignition engine. The engine was operated under Wide Open Throttle (WOT) conditions, with a speed ranging from 2000 to 7000 rpm in increments of 1000 rpm. The length of the ground strap winding on the spark plug cable was 23 cm, while the diameter of the spark plug cable was 0.8 mm, and its length was 23 cm. The data collected were the engine's performance results under standard conditions and at each variation of the ground strap diameter. The findings revealed that the smaller the ground strap diameter, the greater the improvement in engine performance. The provision of a ground strap on the spark plug cable significantly reduces the engine's specific fuel consumption compared to the engine without a ground strap, with an average reduction of 4.451%. Additionally, the air-fuel ratio value deviates from the stoichiometric condition by 9.25% at the best winding of 0.3 mm. On average, installing a ground strap on the spark plug cable also results in an increase in torque and engine power by 5.91% and 6.22%, respectively